Effect of Al doping on the electronic structure and optical properties of germanene. (4th March 2022) - He, Jianlin; Liu, Guili; Wei, Lin; Li, Xinyue
Abstract : The effects of different doping concentrations and hydrogenation on the electronic structure and optical properties of Al-doped germanene were studied based on a density generalised theory first-principles approach. It was found that the system with a doping concentration of 3.125% was more stable. The bandgap is lower than 0.1 eV for doping concentrations of 3.125% to 6.25%, which is consistent with the nature of semimetals. The bandgap transition from indirect-direct-indirect is achieved at doping concentrations of 11.11% to 25%. Both the s- and p-states of Al and Ge atoms contribute to the total density of states compared to the intrinsic germanene, and the doping of Al promotes the absorption and reflection of light from germanene and also undergoes different degrees of blue shift. Hydrogenation has a large effect on the electronic structure of Al-doped germanene, making the s and p state's electronic interactions of Al atoms weaker. The Al-doped germanene system can be converted from indirect bandgap to direct bandgap when fully hydrogenated. GRAPHICAL ABSTRACT: UF0001